The Development of Object Function and Manipulation Knowledge: Evidence from a Semantic Priming Study - Collette, Cynthia; Bonnotte, Isabelle; Jacquemont, Charlotte; Kalénine, Solène; Bartolo, Angela (Frontiers in Psychology, 2016)
Object semantics include object function and manipulation knowledge. Function knowledge refers to the goal attainable by using an object (e.g. the function of a key is to open or close a door) while manipulation knowledge refers to gestures one has to execute to use an object appropriately (e.g. a key is held between the thumb and the index, inserted into the door lock and then turned). To date, several studies have assessed function and manipulation knowledge in brain lesion patients as well as in healthy adult populations. In patients with left brain damage, a double dissociation between these two types of knowledge has been reported; on the other hand, behavioral studies in healthy adults show that function knowledge is processed faster than manipulation knowledge. Empirical evidence has shown that object interaction in children differs from that in adults, suggesting that the access to function and manipulation knowledge in children might also differ. To investigate the development of object function and manipulation knowledge, 51 typically developing 8-9-10 year-old children and 17 healthy young adults were tested on a naming task associated with a semantic priming paradigm (190-ms SOA; prime duration: 90 ms) in which a series of line drawings of manipulable objects were used. Target objects could be preceded by three priming contexts: related (e.g. knife-scissors for function; key-screwdriver for manipulation), unrelated but visually similar (e.g. glasses-scissors; baseball bat-screwdriver), and purely unrelated (e.g. die-scissors; tissue-screwdriver). Results showed a different developmental pattern of function and manipulation priming effects. Function priming effects were not present in children and emerged only in adults, with faster naming responses for targets preceded by objects sharing the same function. In contrast, manipulation priming effects were already present in 8-year-olds with faster naming responses for targets preceded by objects sharing the same manipulation and these decreased linearly between 8 and 10 years of age, 10-year-olds not differing from adults. Overall, results show that the access to object function and manipulation knowledge changes during development by favoring manipulation knowledge in childhood and function knowledge in adulthood.